Peran Kelembagaan Kelompok Sadar Wisata (Pokdarwis) Dalam Pengembangan Objek Wisata Di Kabupaten Kampar - Arlan Suranta Ginting; Hendro Ekwarso; Taryono Taryono (Universitas Mataram, 2025)
This study aims to determine the role of Pokdarwis in increasing public awareness of the importance of sustainable tourism management, examine the factors that support and inhibit the role of Pokdarwis in developing tourism objects in Kampar Regency and analyze innovative strategies implemented by the Tourism Awareness Group (Pokdarwis) in maintaining sustainable tourism in Kampar Regency. Data collection was carried out using observation, documentation and interview techniques using questionnaires. The population of this study was 34 respondents, but the sampling technique used the Purposive Sampling technique and the sample determined from this study was 5 respondents. The research method used is descriptive qualitative. The results of the study indicate that Pokdarwis in Kampar Regency has succeeded in increasing public awareness and increasing the attraction of visits and income, although institutional and regulatory strengthening is still needed to ensure the development of tourism objects in Kampar Regency.